Garlic as A Modern Nursing Complementary Therapy (MNCT) For Hypertensive Patients - Thalib, Abdul; Makatita, Bazrul; Hasan, Hulan; Keliwawa, Sudin; Labulawa, Irman; Papalia, Indah (Alta Dharma Publisher, 2023)
Introduction: Hypertension is a severe problem that needs to be addressed because it is a significant factor causing premature death worldwide. The use of garlic herbs as a treatment for hypertension has been widely done but still needs further research, especially providing the correct dose for patients. Objective: This study aims to find the right amount to treat hypertension, determine the decrease in systole and diastole blood pressure, and see the impact of BMI on lowering blood pressure from garlic therapy. Method: Pre-experimental Design research design with One-group Pretest-posttest Design. The sampling technique was non-probability with a purposive sampling approach. This study consisted of 45 respondents divided into three groups: Group 1 (dose 3gr), Group 2 (dose 6gr), and Group 3 (dose 9 gr). The intervention was carried out by giving garlic steeping to patients with hypertension who were monitored for seven days. Results: There was an effect of garlic steeping on reducing systole blood pressure in group 1 (0.033), group 2 (0.011), and group 3 (0.001) as well as diastole blood pressure, group 1 (0.038) and group 3 (0.034) while in group 2 (0.102) was not significant. Decrease in systole and diastole blood pressure in group 1 10.01±4.67 mmHg in group 2 12±2 mmHg while in group 3 18±4 mmHg. Conclusion: Steeping garlic in all three intervention groups can lower systole and diastole blood pressure, where high doses show more significant blood pressure reductions than low doses. Recommendation: Garlic can be used as a complementary nursing therapy by adjusting the dosage needs according to the patient's blood pressure